The Use Of Hedges By Native And Malay Writers Of English In The Discussion Section Of Academic Articles - Sakinah Mohamad @ Md.Som (Penerbit USIM, Universiti Sains Islam Malaysia, 2024)
International Language and Education Conference 2021 (iLEC’21) e-PROCEEDINGS “Language and Education : New Norms” 2nd & 3rd November 2021 Organized by : Faculty of Major Language Studies (FPBU), USIM Editor: Azalia Zaharuddin, Suhaili A. Jalil, Kirembwe Rashid Abdul Hameed, Wan Azura Wan Ahmad.